TANTANGAN PENANAMAN ADAB DAN ETIKA ANAK JAMAN SEKARANG - Kurniawati, Wahyu; Anisya Al Husna; Prasetyo Riambodo; Budiharti; Rahma Kurnia Novitasari (Jurnal Gembira: Pengabdian Kepada Masyarakat, 2024)
The manners and personality of today's young generation are slowly eroding. The fading of respect, tolerance, manners and ethics. Moreover, the attitude of our young people is also characterized by smoking, the habit of cheating in school and dating, and sometimes participating in brawls. The purpose of this study is the cultivation of manners and ethics in today's children. The method in this research is to use socialization based on case studies. The results of this study All participants of the socialization conducted have understood well the manners and ethics that need to be done in life in society or when in other places, through question and answer all participants of this socialization can understand about views, solutions, and ethics in establishing relationships with others. Through the socialization of the cultivation of ethics, this makes one of the solutions that can be done in preventing, reducing, and healing today's children who have poor ethics.